Deploying Low‐carbon Technologies in Developing Countries: A view from India's buildings sector. (March 2017) - Khosla, Radhika; Sagar, Ambuj; Mathur, Ajay
Abstract: The climate change arena comprises a diverse set of interacting actors from international, national and local levels. The multilevel architecture has implications for low‐carbon technology deployment in developing countries, an issue salient to both development and climate objectives. The paper examines this theme through two inter‐related questions: how do (or don't) low‐carbon technologies get deployed in India's built environment, and what implications can be drawn from the Indian case for effective low‐carbon technology development and transfer for developing countries? By examining the multilevel linkages in India's buildings sector, the paper shows how the interactions between governance levels can both support and hinder technology deployment, ultimately leading to inadequate outcomes. The potential of these linkages is hobbled by aspects of the national context (federated energy governance and developing‐country capacity limitations), yet can also be enabled by other features (the climate policy context, which may motivate international actors to fill domestic capacity lacunae). Reflecting on the India case, the paper makes recommendations for improved low‐carbon technology deployment in developing countries: (1) technology development and transfer collaboration on a 'need‐driven' approach, (2) development of the specific types of capacity required across the entire innovation chain and (3) domestic strengthening of the coordination and agendas across and between governance levels. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment